Maquinical Ensembles in Fugue:: feminisms and performativity in two Andean music groups from Argentina - Podhajcer, Adil; Vega, Alejandra (Revista Brasileira de Estudos da Presença, 2024)
In this article we describe and comparatively analyze the performances of two community Andean music ensembles that represent two regions of Argentina with contrasting characteristics, and that constitute the two most important referents of groups of women and dissidents in Argentina. In this opportunity, we will focus on the performative practices of the women’s Band from Tilcara Nuestra Señora de Fátima, Jujuy, and the Mama Quilla Community, from the Buenos Aires Metropolitan Area. The objective is to understand the relationship between the experience-in-the-world understood as a projection oriented towards a cosmogony with Andean roots and the aesthetic-political qualities that reinstate the question of the scope of dissident feminism to produce other modes of action and political consciousness.